Weather-Induced Mood, Institutional Investors, and Stock Returns - Goetzmann, William N.; Kim, Dasol; Kumar, Alok; Wang, Qin (Review of Financial Studies, 2015)
This study shows that weather-based indicators of mood impact perceptions of mispricing and trading decisions of institutional investors. Using survey and disaggregated trade data, we show that relatively cloudier days increase perceived overpricing in individual stocks and the Dow Jones Industrial Index and increase selling propensities of institutions. We introduce stock-level measures of investor mood; investor optimism positively impacts stock returns among stocks with higher arbitrage costs, and stocks experiencing similar investor mood exhibit return comovement. These findings complement existing studies on how weather impacts stock index returns and identify another channel through which it can manifest.